En poudre ou en blocs ? Matières colorantes et faciès funéraires dans la plaine d’Alsace au Néolithique ancien (5300 à 4950 av. n.è.) - Laura Waldvogel (Frontière·s)
In 1995, the study of the Linearbandkeramik’s (LBK) funerary practices, an archaeological culture of the Early Neolithic originating from the Danube basin, led to the identification of two funeral facies on its western areas. The Alsace plain has thus the particularity to be split into two with a border near the present town of Colmar. For both entities, the shape taken by colorants deposited with the deceased has been seen as a defining factor: in powder form within the facies I, these substances are found in raw or semi-processed blocs in the facies II. Twenty-six years after C. Jeunesse’s article, the review of the Alsatian corpus, which has significantly increased since, and its comparison with the data from necropolises located at the west and the east of this region not only confirm the existence of these facies from stage III, but also allow to identify new distinctive features shared by the Parisian basin and the Haute-Alsace (facies I) regarding the localization of powdered ‘ochre’.